COMPREHENSIVE ANALYSIS OF MAGNETIC AND GRAVITY DATA BASED ON VOLUMETRIC GRAVITY-MAGNETIC MODELING ALONG THE GEOTRAVERSE IN THE SHU-SARYSU SEDIMENTARY BASIN - TLEUBERGENOVA, Aigerim; UMIROVA, Gulzada; MAUSSYMBAYEVA, Aliya; PORTNOV, Vasiliy (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The purpose of the studies presented in the article is to obtain the information of the deep structures along the Shu-Sarysu geotraverse, to determine the regularities in the distribution of mineral deposits and predictive assessment of the research area prospects for searching for hydrocarbons and other minerals. To achieve this purpose, a complex of high-precision gravitational and magnetometric measurements was used. There was shown a high efficiency of the integrated interpretation of 3D gravimagnetic modeling when studying the geological structure of the crystalline basement (assessment of the morphology of its surface, material-petrophysical mapping of the rocks that make up the basement) and the sedimentary cover (assessment of the morphology of the reference horizons, studying their material composition); when identifying and clarifying the position of discontinuous faults, conducting lineament analysis in order to decipher the block structure of the studied areas; when building 3D volumetric models of geophysical parameters; when substantiating predictive and search geophysical criteria for detecting oil and gas geological structures, both in the thickness of sedimentary formations and in the rocks of the crystalline basement. The progress of these methods is conditioned by the widespread introduction into practice of modern computer technologies for processing and interpreting data.